Faktor yang Berhubungan dengan Stimulasi Toilet Training pada Anak Usia Toddler (1-3 Tahun) di Wilayah Kerja Puskesmas Rasimah Ahmad Kota Bukittinggi - Kriscillia Molly Morita; Liza Merianti; Oma Marisa (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Toilet training trains children to control their bowel and bladder. However, many mothers do not carry out toilet training stimulation for toddlers because they do not know the benefits are very great in growing children's independence. Toilet training teaches children to clean their own feces and reuse their pants. The purpose of this study is to find out the factors associated with toilet training stimulation in toddler age children in the Rasimah Ahmad Community Health Center in Bukittinggi in 2019, the factors studied were mother's knowledge, education mother and family support with toilet training stimulation in toddler age children. The research design was descriptive analytic using a cross sectional approach with a sample of 139 mothers, data processing was performed using the Chi-Square test. This study proves that there is a significant relationship between knowledge, education and family support with toilet training stimulation in toddler age children with a PV of 0.001. It is expected that Pukesmas officers and holders of maternal and child health programs will incorporate toilet training into the health education program at the posyandu.